Fundamentals of financial management - Brigham, Eugene F., 1930-; Houston, Joel F. (Australia : Cengage, 2022)
"When the first edition of Fundamentals was published 40 years ago, we wanted to provide an introductory text that students would find interesting and easy to understand. Fundamentals immediately became the leading undergraduate finance text, and it has maintained that position ever since. Our continuing goal with this edition is to produce a book and ancillary package that sets a new standard for finance textbooks. Finance is an exciting and continually changing field. Since the last edition, many important changes have occurred within the global financial environment. In the midst of this changing environment, it is certainly an interesting time to be a finance student. In this latest edition, we highlight and analyze the events leading to these changes from a financial perspective. Although the financial environment is ever-changing, the tried-and-true principles that the book has emphasized over the past four decades are now more important than ever"--
Includes bibliographical references & index.
Keywords: Corporations -- Finance